Das Wettmonopol in Deutschland: Status Quo und Reformansätze - Mario Maschke; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2010)
This paper focuses on the legal monopoly for sporting bets in Germany. We analyze the pricing behavior of the monopolist ODDSET and find that typical pricing inefficiencies on betting markets are reinforced under the monopoly. This result in conjunction with the decreasing tax revenue may motivate a liberalization of betting markets in Germany. We consider several tax designs for a liberalized market and favor gross earnings as tax base.
Keywords: D42; D84; G14; 330; Glücksspiel; Sport; Monopol; Deregulierung; Vergnügungsteuer; Steuerbemessung; Deutschland